A Framework to Define the Impact of Sustainable ICT for Agriculture Projects: The Namibian Livestock Traceability System. Issue 1 (5th December 2017) - Prinsloo, Tania; de Villiers, Carina
Abstract: Namibia expanded its livestock traceability system to include data of the Northern communal farmers, with ear‐tagging starting in 2010, and full functionality added in 2014. The new technology enables them to export safe meat products to previously‐excluded overseas markets. In this article, the complexities of a livestock traceability system are explained to provide one with a sense of the lengths countries like Namibia went through to successfully implement such a system. Next, a new framework is proposed to apply to agricultural development projects, called the Impact‐for‐sustainable agriculture framework, with all the facets of the framework explained. Finally, the framework is applied to the Namibian Livestock Identification and Traceability System (NamLITS), with the focus on the Northern Communal Areas (NCAs). NamLITS is an example of a successful agricultural development project, and it is hoped that this new framework can be applied to other agricultural initiatives.